Nicotinamide protects human beta cells against chemically-induced necrosis, but not against cytokine-induced apoptosis - Hoorens, A.; Pipeleers, D. (Diabetologia, 1999)
Nicotinamide intervention trials are presently undertaken to prevent Type I (insulin-dependent) diabetes in high risk subjects. They are based on studies in rodents reporting nicotinamide protection against beta-cell injury in vitro and in vivo. This study examines whether nicotinamide can protect human beta cells in vitro. At concentrations (2 and 5 mmol/l) to protect rat beta cells against necrosis by streptozotocin or hydrogen peroxide, nicotinamide prevents hydrogen peroxide-induced necrosis of human beta cells. As with rat beta cells, nicotinamide fails to protect human beta cells against apoptosis induced by a combination of the cytokines interleukin-1beta, interferon-gamma and tumour necrosis factor-alpha. In rat beta cells, nicotinamide (2 to 20 mmol/l) was also found to induce apoptosis, in particular during the days following its protection against necrosis; this cytotoxic effect was not observed with human beta cells. These data demonstrate that nicotinamide can protect human beta cells against radical-induced necrosis, but not against cytokine-induced apoptosis. This effect is not associated with a delayed apoptosis as in rat beta cells.